UMP Student Parliament session opens 15 April 15 and ends 16 April 16 2023 - Nor Salwana, Mohammad Idris (UMPSA, 2023)
PEKAN, 15 April 2023 - The 2022/2023 Student Parliament Session begins on 15 April 2023 and ends on 16 April 2023.